Home literacy experiences of low-income, urban, Mexican American kindergarten students - Stowe, Ramona (Kansas State University, 2007)
This qualitative, ethnographic study explored home literacy environments. The following question guided the research: In what ways do literacy activities manifest themselves in homes of low-income, urban, Mexican American kindergarten students? Sub questions helped the researcher further understand the home literacy environment: • As acts of literacy take place in the home, what types of parent-child interactions are occurring? • How does the role of siblings impact the literacy activities that occur in the home? • How does the level of education of the parent effect literacy activities of the home? The research employed qualitative methods of data collection: interviews, participant observation and field notes. Surveys were also used to help understand the home literacy activities. A total of eleven families participated in the research. After completing the survey, the families were contacted and home visits were held. During these home visits, the participant observer asked semi-structured interview questions and also observed a parent-child book reading session. The visits were completed for each family between September, 2006 and March, 2007. Translators were used as needed. The following themes emerged: 1) Reading with My Mom; 2) My Mom Reads and Writes Other Things, Too; 3) We Talk A Lot at My House; 4) We Go to the Library; 5) My Sisters and Brothers Read to Me; 6) I use English and Spanish with My Brothers and Sisters; 7) My Mama Studied to be a Pre-School Teacher. Regardless of education level mothers read to their children, used literacy in other ways, and made sure their children went to the library. Parents also took time to talk with their children and storytelling was evident in the homes. Siblings were important to the literacy development of their kindergarten brothers and sisters by reading to them and building English oral proficiency. The education level of the mother mattered only because of the subject studied after high school. The themes found in the research are described in detail. Discussion, conclusions, implications, and recommendations for further research were provided.
Keywords: Literacy; Home environment of Mexican American Students; Education, Curriculum and Instruction (0727)